2014
DOI: 10.1186/1741-7015-12-61
|View full text |Cite
|
Sign up to set email alerts
|

Obesity survival paradox in pneumonia: a meta-analysis

Abstract: BackgroundIt is unclear whether an ‘obesity survival paradox’ exists for pneumonia. Therefore, we conducted a meta-analysis to assess the associations between increased body mass index (BMI), pneumonia risk, and mortality risk.MethodsCohort studies were identified from the PubMed and Embase databases. Summary relative risks (RRs) with their corresponding 95% confidence intervals (CIs) were calculated using a random effects model.ResultsThirteen cohort studies on pneumonia risk (n = 1,536,623), and ten cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
152
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(164 citation statements)
references
References 45 publications
7
152
2
3
Order By: Relevance
“…Paradoxically, obesity also has been shown to confer a survival benefit once CVD is established . Emerging evidence has demonstrated that obese patients with CVD may have a more favorable prognosis than their normal‐weight counterparts, a phenomenon often termed “obesity paradox.” The obesity paradox has also been confirmed in non‐CVDs, including type 2 diabetes mellitus, hemodialysis, cancer, and pulmonary disease …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Paradoxically, obesity also has been shown to confer a survival benefit once CVD is established . Emerging evidence has demonstrated that obese patients with CVD may have a more favorable prognosis than their normal‐weight counterparts, a phenomenon often termed “obesity paradox.” The obesity paradox has also been confirmed in non‐CVDs, including type 2 diabetes mellitus, hemodialysis, cancer, and pulmonary disease …”
Section: Introductionmentioning
confidence: 92%
“…The obesity paradox has also been confirmed in non-CVDs, including type 2 diabetes mellitus, hemodialysis, cancer, and pulmonary disease. [10][11][12][13] Hypertension is a major public health challenge, especially in developing countries. Successive population surveys in China have indicated that increases in the prevalence of hypertension have been substantial during the past 30 years, with the most recent national survey reporting at least 325 million Chinese adults (29.6%) have hypertension.…”
mentioning
confidence: 99%
“…Not only is there strong evidence for pathogen-induced anorexia but also there is a large body of evidence that individuals carrying more fat have a better chance of survival when they are infected. For example, human mortality from pneumonia in elderly individuals in the 30 days following the contraction of the infection is about 4× higher in underweight individuals (mortality rate 19.4%) compared with individuals with obesity (mortality rate 5.7%) (Nie et al, 2014). Carrying more fat seems to be protective against mortality from many different diseases, both infective and non-communicable: commonly called the obesity paradox (Lavie et al, 2003;Curtis et al, 2005).…”
Section: Dual-intervention Point Model and 'Drifty Gene' Hypothesismentioning
confidence: 99%
“…On the other hand, an inverse relation between obesity and death has been identified in surgical ICUs [9], elective general surgery [10], pneumonia [11], heart failure, coronary heart disease, and patients with diabetes mellitus. Similarly, this finding of the ''obesity paradox'' was identified in patients with surgical peritonitis with improved shortterm but not long-term outcomes [12].…”
Section: Discussionmentioning
confidence: 99%